2020
DOI: 10.1101/cshperspect.a040493
|View full text |Cite
|
Sign up to set email alerts
|

Causal Inference Methods to Integrate Omics and Complex Traits

Abstract: Major biotechnological advances have facilitated a tremendous boost to the collection of (gen-/transcript-/prote-/methyl-/metabol-)omics data in very large sample sizes worldwide. Coordinated efforts have yielded a deluge of studies associating diseases with genetic markers (genome-wide association studies) or with molecular phenotypes. Whereas omics-disease associations have led to biologically meaningful and coherent mechanisms, the identified (non-germline) disease biomarkers may simply be correlates or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 125 publications
(128 reference statements)
0
8
0
Order By: Relevance
“…Several of the other papers in this collection elaborate on some of the novel methodological approaches, including multivariable MR and the use of MR for assessing mediation (Sanderson 2021), polygenic MR methods for assessing pleiotropy , as well as withinfamily MR methods (Hwang et al 2020). Other papers describe the application of the approach for extending clinical applicability and uncovering molecular mechanisms (Porcu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the other papers in this collection elaborate on some of the novel methodological approaches, including multivariable MR and the use of MR for assessing mediation (Sanderson 2021), polygenic MR methods for assessing pleiotropy , as well as withinfamily MR methods (Hwang et al 2020). Other papers describe the application of the approach for extending clinical applicability and uncovering molecular mechanisms (Porcu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to germline genetic variation, -omic signatures are largely phenotypic, and are therefore subject to the same potential problems of confounding and reverse causation that afflict conventional epidemiology (Relton and Davey Smith 2010). MR is being increasingly applied to elucidate causality for a range of molecular data, including epigenetics, transcriptomics, gene expression, metabolomics, and proteomics (Porcu et al 2021). For this, approaches such as two-step, network, and multivariable MR are of particular utility for determining whether these markers lie on the causal pathway between risk factors and disease (Table 4).…”
Section: Uncovering Molecular Mechanismsmentioning
confidence: 99%
“…Note that we define phenotypes broadly as including any individual characteristic other than genotypes, which includes all omics other than genomics. Methods covered in Porcu et al (2021) aim to query the potential of genetically informed methods in elucidating the role of metabolomics as modifiable risk factors for diseases. Such research questions build on largescale and growing data sets and cover much-needed computational tools for causal inference.…”
Section: Contributionsmentioning
confidence: 99%
“…Mapping genetic variants identified in GWAS analyses to biological processes is notoriously difficult [2]. However, systems genetics approaches that integrate multiple omics datasets as a way of leveraging GWAS summary data have proven successful in providing a more complete picture of the path from genotype to phenotype [82]. Here, we demonstrated that our multi-omics framework was able to attribute GWAS signals to biological pathways in loci harbouring multiple genes (e.g.…”
Section: Discussionmentioning
confidence: 84%